The Influence of Transformational Leadership, Compensation, Organizational Commitment on Turnover Intention in Mediation of Job Satisfaction (Study on Manufacturing Company PT XYZ) - Widjaja, Lenda; Ardi Ardi (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This study aims to determine the effect of Transformational Leadership, Compensation, and Organizational Commitment on Turnover Intention, mediated by Job Satisfaction among employees at PT XYZ. The research method used was a quantitative survey approach using a questionnaire distributed to the entire population of 167 employees. The data were analyzed using Structural Equation Modeling Partial Least Squares (SEM-PLS) with the aid of SmartPLS 4.0 software. The results showed that Transformational Leadership and Compensation had a positive effect on Job Satisfaction and a negative effect on Turnover Intention. Furthermore, Job Satisfaction also had a negative effect on Turnover Intention. The conclusion of this study is that the research model used is able to explain the relationship between the independent variables and Turnover Intention and demonstrates that Transformational Leadership and Compensation play a significant role in increasing Job Satisfaction and reducing employee intentions to leave the company. Keywords: Transformational Leadership, Compensation, Job Satisfaction, Turnover Intention